2016
DOI: 10.7150/jca.12663
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Targeting MET Signaling in Solid Tumors - Are We There Yet?

Abstract: The MET signaling pathway plays an important role in normal physiology and its deregulation has proved critical for development of numerous solid tumors. Different technologies have been used to investigate the genomic and proteomic status of MET in cancer patients and its association with disease prognosis. Moreover, with the development of targeted therapeutic drugs, there is an urgent need to identify potential biomarkers for selection of patients who are more likely to derive benefit from these agents. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 113 publications
(205 reference statements)
0
24
0
Order By: Relevance
“…Similarly to clear-cell RCC, MET mutations (and specifically in the exon 14) have not been identified in prostate cancer, while Met expression has been correlated with the castration-resistant tumor proliferation (75,76). Although pre-clinical and early phase trials suggested a potential activity of Met inhibitors in prostate cancer, phase III trials, such as the COMET-1, failed to demonstrate positive results (77).…”
Section: Other Tumorsmentioning
confidence: 99%
“…Similarly to clear-cell RCC, MET mutations (and specifically in the exon 14) have not been identified in prostate cancer, while Met expression has been correlated with the castration-resistant tumor proliferation (75,76). Although pre-clinical and early phase trials suggested a potential activity of Met inhibitors in prostate cancer, phase III trials, such as the COMET-1, failed to demonstrate positive results (77).…”
Section: Other Tumorsmentioning
confidence: 99%
“…A number of MET-targeted TKIs and therapeutic antibodies have entered clinical development, but so far, none have been approved as MET-targeting agents (9). TKIs generally have limited target specificity, which may lead to pleiotropic effects and unwanted toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…We found that activated EGFR, MET, AXL, EPHB1, and EPHB2 were basally detected in HCT116 cells (Figure A, left) and phosphorylated EGFR, MET, ERBB3, Insulin R, and IGF‐1R were basally detected in HT29 cells (Figure A, right). MET is known to be abnormally activated in many cancers, and its activation has been reported to contribute to tumour growth, proliferation, and survival . These patterns were further confirmed by western blot analysis.…”
Section: Discussionmentioning
confidence: 53%
“…MET is known to be abnormally activated in many cancers, and its activation has been reported to contribute to tumour growth, proliferation, and survival. 33,34 These patterns were further confirmed by western blot analysis. Interestingly, phosphorylated MET decreased by paroxetine treatment in both the cell lines, suggesting that MET could be a common target for paroxetine ( Figure 4B).…”
Section: Discussionmentioning
confidence: 55%